2017
DOI: 10.4236/msa.2017.85025
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive WaterJet Machining of Thick Carrara Marble: Cutting Performance vs. Profile, Lagging and WaterJet Angle Assessments

Abstract: This paper deals with an assessment of the machined surface created by abrasive waterjet technology regarding its cutting performance versus profile, lagging and waterjet angle assessments. The results of the experiments presented in this study are with regard to Carrara marble. The machined surfaces were measured in seven different locations across a 40 mm depth of cut by a high precision contact-type profilometer and thus assessed using the standardized amplitude parameters of the profile distribution. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Here, all FDM 3D fabricated parts were measured using a contact-type Taly Details of an engineering surface roughness measurement procedure have been already reported elsewhere [36]- [43] and are only briefly summarized here.…”
Section: Surface Roughness Measurement In Ammentioning
confidence: 99%
“…Here, all FDM 3D fabricated parts were measured using a contact-type Taly Details of an engineering surface roughness measurement procedure have been already reported elsewhere [36]- [43] and are only briefly summarized here.…”
Section: Surface Roughness Measurement In Ammentioning
confidence: 99%
“…The traces were auto-leveled, set up to a linear least-squares (LLS) straight line and then filtered with a standard lowpass of 0.8 mm cut-off wavelength and filter CR ISO. Details of the average surface roughness measurements procedure and calibration trials have been reported elsewhere [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. In general, the calibration results showed that the cantilever beam system (stylus with beam) at only one end was a linear mass-spring system (R 2 > 0.999) under operational and environmental conditions, generally at 20°C ± 1°C temperature and 40% ± 5% relative humidity, with an absolute uncertainties value of < 1% and measurement resolution down to at worst 50 nm.…”
Section: Measuring Methodsmentioning
confidence: 99%
“…The results showed that the angle increased with increasing sample thickness. Alsoufi et al [19] studied the influence of different technological parameters of water-jet machining on the water-jet angle. It was found that the dimension of the area of visible machining marks and their angle increased with increasing the cutting traverse rate and that there was a direct relation between the technological parameters and the jet deflection angle.…”
Section: Introductionmentioning
confidence: 99%